The conception of welcome in social service: a review of CBAS and ENPESS events (Emancipação, 2023)
This article aims to investigate how Social Work in health policy includes welcoming in its theoretical productions. It is characterized as an exploratory study, based on a bibliographic research, with a qualitative approach, fundamental in critical social theory and in the dialectical method of categories. Data collection took place with the survey of productions in the annals of CBAS and ENPESS from 2010 to 2019. Eleven articles were selected, five corresponding to CBAS and six to ENPESS. The productions of the theoretical production on the researched topic, although elaborated, the limits of the study regarding the scarce number found on the theme. It was found that as productions they propose the importance of the welcomingproject, focusing on strengthening the humanization project of the Unified Health System (SUS), linked to the critical professional of Social Work. It was also recognized the spaces for the discussion of reception in which it promotesresearch and the production of knowledge of the category.
Keywords: Multiprofessional Residence. Universitary hospital. Health Policy.